2020
DOI: 10.1186/s12895-020-00120-z
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations after bariatric surgery

Abstract: Background Skin signs observed in morbid obesity may change as the weight reduces, especially post-bariatric surgery (BaS). Data concerning the skin findings exclusively in post-BaS patients remain limited. Methods Seventy post-BaS patients were examined for cutaneous abnormalities. The patients were divided into those with successful weight loss (% excessive body weight loss (EBWL) of at least 50%) and a non-successful group (%EBWL < 50%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…24 Obesityassociated AN may show clinical improvement with weight loss. [25][26][27][28] Our study demonstrated that AN in children with obesity was most frequently located on the neck, a visible area not normally covered with clothing. In light of these findings, we think it important to inform the child and family that AN will improve with weight loss.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…24 Obesityassociated AN may show clinical improvement with weight loss. [25][26][27][28] Our study demonstrated that AN in children with obesity was most frequently located on the neck, a visible area not normally covered with clothing. In light of these findings, we think it important to inform the child and family that AN will improve with weight loss.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to its association with insulin resistance, the appearance of AN may cause psychological distress for the child and the family, including stigmatizing behaviors such as changing dress style to cover up AN 24 . Obesity‐associated AN may show clinical improvement with weight loss 25–28 . Our study demonstrated that AN in children with obesity was most frequently located on the neck, a visible area not normally covered with clothing.…”
Section: Discussionmentioning
confidence: 74%
“…Zinc deficiency resulting from malabsorption in bariatric surgery has been linked to the development of the rare condition known as necrotic migratory erythema ( 74 ). Despite the clinical improvement of acanthosis nigricans, the development of alopecia has been described in a cohort of post bariatric surgery in relation to malabsorption ( 75 ). In post-bariatric abdominoplasty, delayed wound healing, skin infections, and umbilical necrosis have been shown to be significantly correlated with certain predictors such as initial BMI, type 2 diabetes, tobacco smoking, and the amount and timing of abdominoplasty ( 76 ).…”
Section: Adverse Skin Reaction To Anti-obesity Treatmentmentioning
confidence: 99%
“…In terms of AN management, the treatment of the underlying disease represents a stepping stone in improving AN: nutritional and psychological intervention for weight control; bariatric surgery; insulin sensitizers for IR, usually metformin; oral contraceptives in PCOS; or gonadotropin releasing hormone agonist therapy in young populations for hyperandrogenemia [ 48 , 49 , 50 ]. There are also dermatological options (which are not typically used in every day practice), such as topical retinoids or vitamin D analogues, chemical peels (trichloroacetic acid or salicylic–mandelic acid peeling), alexandrite laser, and systemic retinoids [ 28 , 29 , 37 , 51 ].…”
Section: Introductionmentioning
confidence: 99%